Evaluation of the potential of SMART-systems - Uhodnikova, Olena (Technology audit and production reserves, 2017)
The article analyzes the SMART-technologies, used for the development of cities and territories. The topicality of the problem of SMART-technologies use is connected with the necessity of improving the life quality of population by the use of innovative technologies, elaborated in the different fields of science and technique, adapting them to the specificity of cities and territories development. On the base of analysis of the foreign experience and elaboration of the problems of Ukrainian cities there was determined the expedience of using the notion SMART-territory that includes numerous parameters of evaluation and gives the great possibilities for territories development. The use of SMART-territories conception will allow increase the development level of many settlements and will favor the harmonic development of cities-centers and adjacent settlements.